When loud Weather buffeted Naoshima: A Sensory Walk - Kathöfer, Jasmin (Academic Quarter | Akademisk kvarter, 2019)
Walking isn’t just walking. A walk, especially if you don’t concentrate on seeing, stimulates the senses. When musician David Sylvian visited the Japanese island of Naoshima in winter 2006 to record sounds for his ambient track “When loud Weather buffeted Naoshima”, he had in mind that the listener should hear the song with an MP3 player during a slow walk around the island. The recorded sounds should mix with the sounds that are created while walking: noise from cars and other pedestrians, wind, birds and the sound of the sea. The aim of the article is to reflect on the sensory walking experience that accompanies Sylvian’s work. Other sensory sensations, such as the smells of the island and the tactility of the subsoil there, which I collected during a visit in March 2018, should also be taken into account.